(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Sofia Vlad explores literature as an ethical mediator between the Same and the Other, drawing on Emmanuel Levinas and György Lukács. The study argues that while the ancient sense of totality is lost, unity can be regained through a shared literary experience. By critiquing reception theories, the author asserts that literature possesses a universal character rooted in human emotions. Ultimately, the aesthetic experience creates a common space, facilitating authentic communication beyond individual differences. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.